Silica nanoparticles as pesticide against insects of different feeding types and their non-target attraction of predators - Ahmed F. Thabet (Nature Portfolio, 2021)
Abstract The agricultural use of silica (SiO2) nanoparticles (NPs) has the potential to control insect pests while the safety and tritrophic effects on plants and beneficial natural enemies remains unknown. Here, we evaluate the effects of silica NPs on insect pests with different feeding niches, natural enemies, and a plant. Silica NPs were applied at different concentrations (75–425 mg/L) on field-cultivated faba bean and soybean for two growing seasons. The faba bean pests, the cowpea aphid Aphis craccivora and the American serpentine leafminer Liriomyza trifolii, and the soybean pest, the cotton leafworm Spodoptera littoralis, were monitored along with their associated predators. Additional laboratory experiments were performed to test the effects of silica NPs on the growth of faba bean seedlings and to determine whether the rove beetle Paederus fuscipes is attracted to cotton leafworm-infested soybean treated with silica NPs. In the field experiments, silica NPs reduced the populations of all three insect pests and their associated predators, including rove beetles, as the concentration of silica NPs increased. In soybean fields, however, the total number of predators initially increased after applying the lowest concentration. An olfactometer-based choice test found that rove beetles were more likely to move towards an herbivore-infested plant treated with silica NPs than to a water-treated control, suggesting that silica NPs enhance the attraction of natural enemies via herbivore-induced plant volatiles. In the laboratory, while silica NPs inhibited the development of faba bean roots at 400 mg/L, they did not affect germination percentage, germination time, shoot length, or vigor index compared to the control.